2008
DOI: 10.1002/hed.20770
|View full text |Cite
|
Sign up to set email alerts
|

Using fluorodeoxythymidine to monitor anti‐EGFR inhibitor therapy in squamous cell carcinoma xenografts

Abstract: Background-3′-18F-fluoro-3′-deoxy-fluorothymidine ( 18 F-FLT), a nucleoside analog, could monitor effects of molecularly targeted therapeutics on tumor proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…This was in agreement with the study reported by Li et al [42]. Although we did not look at the effect of erlotinib treatment on EGFR expression in vivo, other studies reported no significant difference in EGFR expression between erlotinib-treated and placebo groups [43] at the same concentration of erlotinib and in the same tumor model. However, downregulation of total EGFR expression was reported only at a high concentration of erlotinib (20 μM) in vitro [42]; the mechanism by which this occurs remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with the study reported by Li et al [42]. Although we did not look at the effect of erlotinib treatment on EGFR expression in vivo, other studies reported no significant difference in EGFR expression between erlotinib-treated and placebo groups [43] at the same concentration of erlotinib and in the same tumor model. However, downregulation of total EGFR expression was reported only at a high concentration of erlotinib (20 μM) in vitro [42]; the mechanism by which this occurs remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…This could lead to the use of a more specific marker of cell proliferation, such as 3-deoxy-3-18 F-fluorothymidine (29). Indeed, Atkinson et al (30) reported that 3-deoxy-3-18 F-fluorothymidine allowed anti-EGFR inhibitor therapy in squamous cell carcinoma to be monitored. However, 3-deoxy-3-18 F-fluorothymidine is not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…When nude mice bearing the human squamous cell cancer graft (HNX-OE; nu/nu mice) were irradiated, both 18 F-FDG and 18 F-FLT uptake declined from baseline levels, but the decline in 18 F-FDG uptake occurred mainly during the first week of treatment, whereas the greatest decline in 18 F-FLT uptake was noted during the second treatment week (100). In another study, however, 18 F-FLT PET showed promise in assessing the early response to cetuximab in a squamous cell cancer xenograft model (101). A significant decline in tumor SUV, tumor-to-muscle ratios, and thymidine kinase-1 activity occurred as early as 6 d after single-agent therapy had been initiated with cetuximab.…”
Section: F-fltmentioning
confidence: 99%